(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2019)
This study was conducted to examine the effect of the ointment containing Solanum melongena peel extract in the treatment of arsenical keratosis. In total, 23 patients were enrolled on the basis of inclusion and exclusion criteria. The ointment was given to each patient and advised him/her to apply to the site of lesion twice daily for 12 weeks without any gap. The size of the lesion and its photograph were collected before and at the end of the study. The mean (± SD) diameter of the lesion was 3.9 ± 2.1 cm which reduced to 1.8 ± 1.3 cm (reduction 54%). The results were statistically significant. In conclusion, S. melongena peel extract is found to be effective in the treatment of arsenical keratosis.